Naskah Hadis Aceh - Suparwany Suparwany (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2020)
The current trend of researching on Acehnese manuscripts still shed a light on historical, war, and mysticism texts, while hadith ancient texts seem do not entice much attentions of philologists both from outside and within Aceh. This is due to the fact; perhaps the researchers unaware of their existences. Another possibility refers to the presumption; that the discussion of hadith in the past was inclusive within other Islamic scientific studies. Using the literary method, this article examines the trends in writing, researching and conservation of post-Tsunami Aceh hadith texts. As a result it was stated that research on hadith texts in Aceh requires more comprehensive studies considering the inventory of hadith texts is available in several places in Aceh such as the manuscript of Fawāid Al-Bahīyah by Shaykh Ar-Raniry, Syarah Lathīf 'ala Arba'in Hadithan lil Imam An- Nawawi and Mawa'id al-Badi 'by Syeikh Abdul Rauf Al-Jawi Al-Singkili, Sanad Riyāḍ al-ṣalihīn Li al-Imam An-Nawawi Shaykh Ibn Ahmad Al-Fasangani Al-Atsyi by Tgk Chik Awee Geutah, Kitab Iqadh al -Faqilin by Shaykh Ibrahim, Syifa 'al-Qulub and Lubab al-Hadith by Shaykh Abdullah Ba'id Al-Asyi, and Hadīṡ Arba’īn and Kitab Jauhar Al-Nawawir as Pedir Museum collection.